2014
DOI: 10.1121/1.4898428
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shifts of sonar attention byPipistrellus abramusduring natural hunting for multiple prey

Abstract: Flight paths of echolocating Japanese house bats, Pipistrellus abramus, were tracked during insect hunting in a natural setting using a 32-microphone array. The array surrounded the foraging area, locating each bat, and determined the directional aim of the sonar beam. Successive interceptions, indicated by feeding "buzzes" and post-buzz pauses, occurred singly at intervals from over 20 s down to multiple interceptions at 2-3 s intervals. Bats flew on looping, curved paths. Turning radius tightened as rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 29 publications
7
46
0
Order By: Relevance
“…The Japanese pipistrelle bat (Pipistrellus abramus) increased its body weight by up to ∼20% during nightly foraging (20). We previously reported that P. abramus are capable of capturing prey every 2-3 s (15,21). In this study, we have shown that the bats select flight paths to efficiently capture consecutive prey items.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The Japanese pipistrelle bat (Pipistrellus abramus) increased its body weight by up to ∼20% during nightly foraging (20). We previously reported that P. abramus are capable of capturing prey every 2-3 s (15,21). In this study, we have shown that the bats select flight paths to efficiently capture consecutive prey items.…”
Section: Discussionmentioning
confidence: 79%
“…For multiple targets, it is beneficial for bats in the wild to distribute their sonar attention and flight attention among multiple targets and to plan the future flight path based on the next prey for effective foraging. On the other hand, pipistrelle bats in the wild alternately and rapidly shift their sonar attention (15,22). This fact suggests that bats process echo streams from multiple targets in a time-sharing manner and then select the optimal flight path to capture and hunt a lot of airborne insects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, by analyzing the distribution of retrogradely labeled cells inside the IC, we identified cell types that make long‐range intrinsic connection inside the IC. Although this species have been used frequently on biosonar studies (Fujioka et al., 2014; Sumiya, Fujioka, Motoi, Kondo, & Hiryu, 2017; Takahashi et al., 2014; Yamada, Hiryu, & Watanabe, 2016), the information about the organization of auditory pathways of this species has not been reported except for a single unit recording study from the IC (Goto, Hiryu, & Riquimaroux, 2010). Therefore, our study will give new neuroethological insights on biosonar.…”
Section: Introductionmentioning
confidence: 99%